2021
DOI: 10.1007/s12630-021-02165-1
|View full text |Cite
|
Sign up to set email alerts
|

The association of thrombin generation with bleeding outcomes in cardiac surgery: a prospective observational study

Abstract: Background Cardiac surgery with cardiopulmonary bypass (CPB) is associated with coagulopathic bleeding. Impaired thrombin generation may be an important cause of coagulopathic bleeding but is poorly measured by existing hemostatic assays. We examined thrombin generation during cardiac surgery, using calibrated automated thrombography, and its association with bleeding outcomes. MethodsWe conducted a prospective observational study in 100 patients undergoing cardiac surgery with CPB. Calibrated automated thromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
0
1
Order By: Relevance
“…A ratio of 0.2 of ETP measured at post-CPB versus pre-CPB has been shown to be significantly associated with chest drain output. 11 In our study, no significant relationship was found between the post-CPB/pre-CPB ETP ratio and post-operative blood loss. Instead, the T4/T1 ratio of MCF-EXTEM values and the T1/T4 ratio of CFT-EXTEM values differentiated patients with high and low blood loss.…”
Section: Discussioncontrasting
confidence: 66%
“…A ratio of 0.2 of ETP measured at post-CPB versus pre-CPB has been shown to be significantly associated with chest drain output. 11 In our study, no significant relationship was found between the post-CPB/pre-CPB ETP ratio and post-operative blood loss. Instead, the T4/T1 ratio of MCF-EXTEM values and the T1/T4 ratio of CFT-EXTEM values differentiated patients with high and low blood loss.…”
Section: Discussioncontrasting
confidence: 66%